Characterization and signaling pathway analysis of interferon-kappa in bovine. (February 2017) - Guo, Yongli; An, Dong; Liu, Ying; Bao, Jun; Luo, Xiuxin; Cheng, Xintong; Wang, Yujiao; Gao, Mingchun; Wang, Junwei
Abstract: A bovine interferon-kappa (BoIFN-κ) gene was amplified, which encodes a protein of 215 amino acids sharing 63% identity with human IFN-κ. BoIFN-κ was demonstrated to have antiviral and antiproliferative activities. Moreover, BoIFN-κ was shown to be highly sensitive to trypsin, however, it remained stable despite changes in pH and temperature. Result showed that BoIFN-κ can bind with bovine type I IFN receptors, and the antiviral activity can be blocked by antibodies against type I IFN receptors or BoIFN-κ. Additionally, BoIFN-κ can induce the transcription of Mx1, ISG15 and ISG56 gene, as well as the expression of Mx1 protein. The NF-κB, ISRE, and BoIFN-β promoter can all be activated by BoIFN-κ. This study revealed that BoIFN-κ exhibits the typical characteristics of type I IFNs and exerts antiviral activity via activation of the JAK-STAT signaling pathway. Overall, these findings will enrich the current knowledge about IFN-κ and facilitate further research on the role of type I IFN in antiviral defense responses in bovine. Highlights: BoIFN-κ has the typical characterization of type I interferon. The second exon of BoIFN-κ gene encodes no amino acid. BoIFN-κ has antiviral activity and antiproliferative activity. BoIFN-κ can bind with bovine type I IFN receptors. BoIFN-κ exerts antiviral activity by activating the NF-κB, ISRE, and BoIFN-β promoter.